A Case Report of External Cardiac Pads Used for Internal Cardiac Defibrillation During Resuscitative Thoracotomy. Issue 1 (22nd October 2021) - Brown, Samuel; Mool, Jason L; Young, William E; Hollensteiner, Kourtney M; Cyr, Ashley; Yi, Fia; Gausepohl, Andrew J
ABSTRACT: This is a case report regarding the use of non-conventional methods to perform internal cardiac defibrillation on a trauma patient in an austere environment. The patient was a polytrauma causality of an improvised explosive device who arrived to a far forward resuscitative surgical team during a recent armed conflict. After arrival, the patient lost pulses. An emergency resuscitative thoracotomy was performed, and the patient was noted to have ventricular fibrillation on direct cardiac visualization. In the absence of standard surgical defibrillation paddles, the team applied external defibrillator stickers directly to the patient's myocardium to deliver an electrical shock. The procedure successfully led to the return of spontaneous circulation. This report highlights a novel approach to resuscitation in resource-limited environments by a military surgical team.